Capacity Development Roadmap for Strengthening Stakeholder Skills, Knowledge, and Resilience of Mixed Farming Systems in Malawi - Kachali, Righteous; Chimonyo, Vimbayi (CGIAR, 2024)
The CGIAR Mixed Farming Systems Initiative seeks to improve the productivity, income, and resilience of mixed farming systems in Malawi. Studies have shown that this nexus is achievable through increased adoption and effective utilization of advanced agricultural technologies, supported by well-informed decision-making at all levels of the agricultural value chain. Achieving this vision relies on equipping stakeholders with the necessary skills and knowledge to manage these technologies and navigate the complexities of agricultural systems. To support this, a comprehensive capacity needs assessment was conducted, identifying skill and knowledge gaps across stakeholders in Malawi's mixed farming landscape. Based on these findings, this document presents a Capacity Development Roadmap that outlines tools and methods for targeted interventions. These interventions are tailored to enhance the roles and contributions of farmers, researchers, extension workers, cooperatives, financial institutions, am9ong other players of the mixed farming landscape in Malawi.